2014
DOI: 10.1007/s00436-014-4233-x
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis: killing of newborn larvae by lung cells

Abstract: The migratory stage of Trichinella spiralis, the newborn larva (NBL), travels along the pulmonary microvascular system on its way to the skeletal muscle cells. The present work studies the capability of lung cells to kill NBL. For this purpose, in vitro cytotoxicity assays were performed using NBL, lung cell suspensions from Wistar rats, rat anti-NBL surface sera, and fresh serum as complement source. The cytotoxic activity of lung cells from rats infected on day 6 p.i. was compared with that from noninfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
3
14
0
Order By: Relevance
“…Previous studies demonstrated that ADCC-mediated destruction of T. spiralis NBL was dependent on specific anti- Trichinella IgG [ 62 , 63 ]. Cytotoxicity against NBL in the lungs of T. spiralis- infected mice was found to be IgE-mediated by Falduto et al [ 64 ]. To investigate the cytotoxicity of anti-rTsSPI antibodies, an in vitro ADCC test was also performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that ADCC-mediated destruction of T. spiralis NBL was dependent on specific anti- Trichinella IgG [ 62 , 63 ]. Cytotoxicity against NBL in the lungs of T. spiralis- infected mice was found to be IgE-mediated by Falduto et al [ 64 ]. To investigate the cytotoxicity of anti-rTsSPI antibodies, an in vitro ADCC test was also performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Research both in vivo and in vitro has proved that eosinophil‐damage and neutrophil‐mediated damage of new‐born larvae (NBL) of T. spiralis are dependent on parasite‐specific IgG . Cytotoxic attack against NBLs in the lung of infected mice is IgE dependent . It has been reported that IgM involved in dislodging several kinds of worms.…”
Section: Discussionmentioning
confidence: 99%
“…33 Cytotoxic attack against NBLs in the lung of infected mice is IgE dependent. 34 It has been reported that IgM involved in dislodging several kinds of worms. For example, IgM antibodies were protective against S. stercoralis, Brugia pahangi and Brugia malayi.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn larvae (NBL) were obtained as described previously [21]. Briefly, AW were recovered from the intestine of rats 5-6 days after oral infection with 7000 ML.…”
Section: Newborn Larvaementioning
confidence: 99%